Millennial disturbance-driven forest stand dynamics in the Eastern Canadian taiga reconstructed from subfossil logs - GENNARETTI, Fabio; Arseneault, Dominique; Bégin, Yves (Journal of Ecology, 2014)
International audience 1. Although wildfire is the main natural disturbance factor driving changes in the North American boreal forest, understanding how the fire history of the last millennium shaped the present-day landscape diversity is a difficult task due to the lack of palaeoecological reconstructions with high spatial (few hundreds of square metres) and temporal (annual) resolutions. 2. We combined a detailed inventory of the present-day lakeshore forest of two lakes of the Eastern Canadian taiga with the dendrochronological dating of the subfossil logs that accumulated in the lit-toral zones facing these shores. Our objective was to compare the millennial impact of wildfires among stands of various structures and compositions. Past stem densities and fire years were reconstructed from log recruitment rates and dating of charred logs. 3. Multivariate analysis of the present-day lakeshore forest revealed three and two homogeneous shore segments per site (i.e. clusters). Cluster 1 at both sites exhibited denser forest, higher dead wood values and a higher percentage of balsam fir, a fire-sensitive species. 4. In total, 426 and 611 subfossil logs (mostly black spruce) were crossdated over the last ~1400 years. Their dendrochronological analysis confirmed that each lakeshore cluster, identified from the traits of the present-day forest, experienced a specific fire history over the last millennium (i.e. 0–5 fires of variable severity) that locally influenced forest composition, tree density and growth. Each fire triggered a specific forest structure trajectory characterized by a different stem density and rate of recovery. 5. Synthesis. This study provides a long-term perspective that helps explain how the present-day landscape diversity in the Eastern Canadian taiga reflects the site-specific fire history over the last millennium. Fires have caused persistent and cumulative impacts resulting in a progressive opening of the forest cover along with balsam fir exclusion. Present-day landscapes are mosaics of ...